FOOD PRODUCTION AND PROCESSING TECHNOLOGY - Rahimova Aziza Rashidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, we explore key technological advances in food production and processing, highlighting their impact on improving efficiency, quality, and sustainability in the food industry. From precision agriculture and vertical farming to automation and blockchain technology, we explore cutting-edge tools and strategies shaping the future of food production and processing.